2018
DOI: 10.1002/jcph.1148
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions Reported by Healthcare Professionals: Reaction Characteristics and Time to Reporting

Abstract: We describe adverse drug reaction (ADR) reporting characteristics and factors contributing to length of time to report by healthcare professionals. This is a retrospective study of voluntary reports to an Australian healthcare ADR Review Committee over a 2-year period (2015-2016). Descriptive and univariate models were used for outcomes, employing standardized ADR definitions. Hospital pharmacists reported 84.8% of the 555 ADRs: 70.3% were hospital onset reactions, and 71.7% were at least of moderate severity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 32 publications
2
25
1
2
Order By: Relevance
“…13,14 In question 3, recognizing the patient had SJS/TEN was the crucial first step in identifying the culprit drug as allopurinol, accounting for a latency period of at least 2 weeks before onset of symptoms because of it being a delayed-type T-cell-mediated disorder. 9,15,16 Those lacking the understanding of this clinical syndrome and associated pathogenic mechanism mistakenly identified the beta-lactams, commenced immediately before the onset of symptoms, as the causative drug (protopathic effect). In the second case, respondents who failed to recognize the waxing and waning nature of DRESS syndrome 13 mistakenly attributed the reaction to other antibiotics that coincided with the flare of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 In question 3, recognizing the patient had SJS/TEN was the crucial first step in identifying the culprit drug as allopurinol, accounting for a latency period of at least 2 weeks before onset of symptoms because of it being a delayed-type T-cell-mediated disorder. 9,15,16 Those lacking the understanding of this clinical syndrome and associated pathogenic mechanism mistakenly identified the beta-lactams, commenced immediately before the onset of symptoms, as the causative drug (protopathic effect). In the second case, respondents who failed to recognize the waxing and waning nature of DRESS syndrome 13 mistakenly attributed the reaction to other antibiotics that coincided with the flare of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted HCP assessment of severe DHRs is suboptimal. 8,9 This study sought to identify knowledge gaps in HCPs involved in the management of severe DHRs, focusing on 4 main knowledge domains: (1) drug hypersensitivity syndrome recognition, (2) causality attribution, (3) cross-reactivity patterns, and (4) appropriate diagnostic tests and therapy. We propose that by identifying these knowledge gaps, targeted multidisciplinary education and practice improvement programs can be further developed to improve safe medication management and treatment of these potentially life-threatening conditions.…”
mentioning
confidence: 99%
“…The study cohort was taken from inpatient admissions and Emergency Department (ED) presentations at a university‐affiliated tertiary metropolitan 800‐bed hospital network with state‐wide specialty referral services. Reporting of adverse drug reactions (ADRs) is actively encouraged within the hospital network, with pharmacists supplying 85% of the voluntary ADR reports . For over 10 years, a multidisciplinary ADR Review Committee (ADRRC) has met every 2 weeks to prospectively review ADRs reported, determine causality, and make recommendations .…”
Section: Settingmentioning
confidence: 99%
“…Several risk factors may contribute to the development of cutaneous drug reactions, including multiple drugs consumption, older age, female gender and viral infection . The drugs most commonly incriminated are anti‐microbial drugs, non‐steroidal anti‐inflammatory drugs and analgesics . ACDRs are associated with diverse morphologic patterns and clinical manifestations .…”
Section: Introductionmentioning
confidence: 99%
“…5,[8][9][10][11][12][13][14] The drugs most commonly incriminated are anti-microbial drugs, non-steroidal anti-inflammatory drugs and analgesics. 3,8,[14][15][16][17][18] ACDRs are associated with diverse morphologic patterns and clinical manifestations. [19][20][21][22] They have been shown to result from either immunological aberrant responses (IgE-dependent, immune complex-mediated, cytotoxic or cellular immune mechanisms) or to be mediated by non-immunologic mechanisms (drug overdose, cumulative toxicity, drug interactions, exacerbation of pre-existing skin disease or activation of effector pathways).…”
Section: Introductionmentioning
confidence: 99%